East Central Kansas Experiment Field - Eric Adee (Kansas Agricultural Experiment Station Research Reports, 2025)
This report includes the annual summary of precipitation and temperatures from 2024 at the research locations represented in the 2025 Field Research Report and further details about the Kansas River Valley locations and the east central Kansas locations.
Keywords: East Central Kansas; Kansas State experiment field; Kaw River Valley; Kansas State Experiment Field; 2024 growing season weather; Kansas weather